Poliester tak jenuh sebagai bahan baku pembuatan helm pengaman - Nadilah, Sri; Winursito, Isananto; Wahyuni, Sri; Budiasih, Sri; Purwanti, Christiana Maria Herry (Majalah Kulit, Karet, dan Plastik, 2003)
Unsaturated polyester is applied in many products such as aircraft sections, boats, building, panels, automotive accessories and modifications, etc. In this research, unsaturated polyester was used as a raw material, which was reinforced with a fiberglass mat, and casted in a silicon rubber mold. The concentrations of methyl ethyl ketone peroxide (1-3 phr) as an initiator and cobalt naphtanate (0-2 phr) as an accelerator were used in the preparation of safety helmet. Subsequently, the effects of the compounds to the reaction time, the brittleness of the products, an the physical properties, were studied. The results showed that the compound composed by 100 phr unsaturated polyester, 2 phr methyl ethyl ketone peroxide, 2 phr cobalt naphtanate, 40 phr silica, 20 phr fiberglass mat and 1 phr pigment was not brittle, had a good reaction time and nonflammable, gave 4.82 mm in resistance to penetration, and the deflection of A and B were 4.5 and 0.0 mm, respectively. Keywords : unsaturated polyester, safety helmet, methyl ethyl ketone peroxide, cobalt-naphtenate.